Client Artwork to Understand Anxiety Difficulties: A Case Study - Natri Sutanti; Yang Peng; Luky Kurniawan (Epistema, 2023)
The case study aims to demonstrate a systematic reflective narration of a practice from a trainee person-centred therapist working with a client experiencing some anxiety difficulties through exploring the client’s artwork. The client, named ‘Jack’ for the purposes of this case study, was a white male aged 25 years old living with his parents. The therapist was the author of this case study and worked with Jack in 35 sessions. The researchers of this case study were Jack’s therapist, a fellow therapist and one of the outside counsellors. There were some important findings in this study 1) understanding the artwork could open the experience of client about his anxiety; 2) acknowledging the genuine intention when working with him was considerably effective to limit the expectation of making a perfect therapy and only focused on understanding his frame of reference; 3) unconditional positive regard took the most important part when working with Jack who experienced several anxiety difficulties; 4) acknowledging the different of the cultural background was also important to avoid the unintentional transfer of value which can interfere with the client process; and 5) the last is that being honest with the therapist in the reflective process in supervision and personal therapy was the best way to deal with practical issues in the placement.